Narrative Curriculum and Technologies in Teacher Training: Theoretical and Conceptual Reflections - Rodrigues, Alessandra; Almeida, Maria Elizabeth Bianconcini de (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This theoretical essay aims to develop a reflection based on a theoretical discussion about the concept of narrative curriculum, coined by Ivor Goodson, but still little explored in depth with regards to its possibilities of implementation and materialization in educational contexts. This is a document resulting from the theoretical deepening drawn from a critical-reflective reading of Goodson's works dedicated to the concept. The study reflects on the narrative curriculum and conceptually considers it as an "in-between" place for producing subjectivities and knowledge forming the midst of the construction of the curriculum, but which promotes the authorship and the emancipation of subjects through a formative, dialogical, and dialectical experience of narratively making and revealing the world and the subjects, oneself and others. It is also oriented by guiding questions of deeper reflections aimed at recognizing and organizing the characteristics of two elements which are essential for the integration of the narrative curriculum and Digital Information and Communication Technologies [DICT]: the narrative learning and the narrative capital, which are influenced by the use of DICT as instruments for mediating the constructive process of curricular and learning narratives.